DETECTION OF POTATO VIRUS Y INFECTION USING IMMUNOCHROMATOGRAPHIC ASSAY - N.I. Shonazarova; F.B. Eshboev; V.B. Fayziev; E.I. Yuldashev (Western European Studies, 2025)
It is well known that in the modern era, the continuous expansion of the distribution range of phytopathogenic viruses necessitates the use of rapid diagnostic methods with high sensitivity for their detection. This, in turn, requires the development of reliable and efficient tools for early diagnosis. Therefore, sensitive approaches such as polymerase chain reaction (PCR) and immunological methods (ELISA, immunochromatographic tests) have been widely applied. In the present study, we report the results of detecting Potato virus Y (PVY) using the immunochromatographic assay, which is considered a rapid and convenient method. Its effectiveness and applicability were scientifically evaluated and discussed. During the study, samples were collected from artificially inoculated indicator plants exhibiting disease symptoms, as well as from naturally growing reservoir plants found in virus-infected potato fields and along field margins. These samples were tested using the ImmunoStrip lateral flow assay system. The analysis revealed that the presence of two red signals (lines) on the test strips clearly indicated virus infection in the examined plants. The application of the ImmunoStrip method under field conditions demonstrated that Potato virus Y can be rapidly detected, making this approach an important diagnostic tool for monitoring and preventing the spread of the virus. According to the research results, Potato Virus Y (PVY) was detected in 64% of the plants tested using the ImmunoStrip test. Additionally, a weak viral reaction was observed in 18% of the plants, while the virus was not detected in the remaining 18% of the samples. These results confirm the widespread prevalence of PVY
Keywords: Potato virus Y; indicator plants; reservoir plants; polymerase chain reaction